TENPIN BOWLING - Science and fitness (2004)
This site compiles expertise from the many different disciplines of sport science. There is the area of biomechanics, which helps to analyse your technique, aided by a better understanding of the physics of ball movement. Exercise Physiologists give advice to help bowlers develop physically through fitness training and fitness testing. The all important mental aspect of the game is covered by sport psychology, To complete to total body approach, sports nutrition keeps your body well fuelled and ready to perform at your best.